Llamar al barrio (2020)
This urban renewal project to be developed in the Los Andes neighborhood of the city of Bogotá, proposes housing and commerce to achieve the integration of the neighborhood's population and the attraction of new populations to the sector. Currently in the Los Andes neighborhood there is a great perception of barriers in space, which is caused by the enclosures that exist around the house, which limit the relationships between them, the population of the neighborhood and the public space. On the other hand, the lack of uses other than the residential one reduces the performance of activities that allow relationships and personal interactions, resulting in the lack of a sense of community in the neighborhood. Call the neighborhood seeks to take advantage of its strategic location to be conceived as the entry point to the neighborhood from the side of Calle 80. For which it proposes a program based on the development of housing, services and commerce...